Demobilising the nation: The decline of sovereignty in Western Europe - Heartfield, James (International politics (Hague, Netherlands), 2009)
Sovereignty is the subject of considerable debate in both International Relations (IR) theory and European Union (EU) studies. In IR, debate is oriented around the extent to which sovereignty constitutes the building block – or generative grammar – of international order. In EU studies, inter-governmentalists and integrationalists differ over how, why and to what extent European states are pooling or derogating sovereignty to supra-national institutions. This article makes no claim to resolving these debates. Rather, it works within them in order to examine the ways in which the exercise of sovereignty is becoming increasingly problematic, particularly in Western Europe. Specifically, it is argued, because of the failure of domestic political processes, European states are frustrated in terms of their international actions. This diminution of sovereignty provides the integration process with a veneer of dynamism as European institutions fill the vacuum left by demobilising nation-states.